Mechanisms of Copper Tolerance, Accumulation, and Detoxification in the Marine Macroalga Ulva Compressa (Chlorophyta): 20 Years of Research - Moenne-Munoz, A; Laporte-Poblete, D; Gonzalez-Figueroa, A; Gomez-Luna, M; Espinoza-Majmud, D (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Copper induces an oxidative stress condition in the marine alga Ulva compressa that is due to the production of superoxide anions and hydrogen peroxide, mainly in organelles. The increase in hydrogen peroxide is accompanied by increases in intracellular calcium and nitric oxide, and there is a crosstalk among these signals. The increase in intracellular calcium activates signaling pathways involving Calmodulin‐dependent Protein Kinases (CaMKs) and Calcium‐Dependent Protein Kinases (CDPKs), leading to activation of gene expression of antioxidant enzymes and enzymes involved in ascorbate (ASC) and glutathione (GSH) synthesis. It was recently shown that copper also activates Mitogen‐Activated Protein Kinases (MAPKs) that participate in the increase in the expression of antioxidant enzymes. The increase in gene expression leads to enhanced activities of antioxidant enzymes and to enhanced levels of ASC and GSH. In addition, copper induces an increase in photosynthesis leading to an increase in the leve of Nicotinamide Adenine Dinucleotide Phosphate (NADPH). Copper also induces an increase in activities of enzymes involved in C, N, and S assimilation, allowing the replacement of proteins damaged by oxidative stress. The accumulation of copper in acute exposure involved increases in GSH, phytochelatins (PCs), and metallothioneins (MTs) whereas the accumulation of copper in chronic exposure involved only MTs. Acute and chronic copper exposure induced the accumulation of copper‐containing particles in chloroplasts. On the other hand, copper is extruded from the alga with an equimolar amount of GSH. Thus, the increases in activities of antioxidant enzymes, in ASC, GSH, and NADPH levels, and in C, N, and S assimilation, the accumulation of copper‐containing particles in chloroplasts, and the extrusion of copper ions from the alga constitute essential mechanisms that participate in the buffering of copper‐induced oxidative stress in U. compressa. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.